2013
DOI: 10.1111/apha.12139
|View full text |Cite
|
Sign up to set email alerts
|

Vaspin prevents methylglyoxal‐induced apoptosis in human vascular endothelial cells by inhibiting reactive oxygen species generation

Abstract: The present results for the first time demonstrate that vaspin inhibits MGO-induced EC apoptosis by preventing caspase-3 activation via the inhibition of NOX-derived ROS generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 27 publications
9
46
0
Order By: Relevance
“…Using the fluorescent probes DCF and DHE, we also detected high levels of hydrogen peroxide and superoxide formation when HUVECs were stimulated prior to the time point (within 1 h) that apoptotic cell death became evident. Our results are in agreement with previous studies showing ROS generation as an important upstream signal molecule in MGO-induced apoptosis [17, 18, 31, 32]. In our experiments, both AGE inhibitors LR-90 and AG suppressed ROS formation and associated mitochondrial-dependent cell death signaling pathway.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Using the fluorescent probes DCF and DHE, we also detected high levels of hydrogen peroxide and superoxide formation when HUVECs were stimulated prior to the time point (within 1 h) that apoptotic cell death became evident. Our results are in agreement with previous studies showing ROS generation as an important upstream signal molecule in MGO-induced apoptosis [17, 18, 31, 32]. In our experiments, both AGE inhibitors LR-90 and AG suppressed ROS formation and associated mitochondrial-dependent cell death signaling pathway.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that MGO can induce apoptosis in human vascular ECs [1517], and that this cytotoxic effect occurs mainly through induction of reactive oxygen species (ROS) [15, 1719], although the molecular mechanism underlying this process is not yet fully understood. The aim of this study was to examine whether LR-90, an AGE inhibitor with pleiotropic properties (antioxidant, anti-inflammatory, carbonyl scavenger) [2023] could exert a cytoprotective effect on the endothelium by inhibiting apoptosis induced by MGO, and to investigate its effects on the various signaling pathways associated with apoptosis, including oxidative stress, MAPK and caspase activation, and mitochondrial-dependent cell death signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Also, vaspin protects ECs against NEFA-induced apoptosis via activation of PI 3 k/Akt signaling pathway [322]. Consistently, vaspin diminishes methylglyoxal-induced apoptotic activity in ECs by inhibiting caspase-3 activation through inhibition of Nox-mediated ROS generation [323]. Taken [325,326], confirming the anti-inflammatory role of vaspin on ECs.…”
Section: Vaspinmentioning
confidence: 78%
“…In contrast, increase of NOX activity (Lassegue & Clempus 2003) or inactivation of SOD or GPx (Forgione et al 2002, Lob et al 2010) induces oxidative stress causing vascular inflammatory responses. We have previously demonstrated that vaspin prevented apoptosis mediated by methylglyoxal, a metabolite of glucose via the inhibition of NOX activity in vascular endothelial cells (Phalitakul et al 2013). In the present study, we found that vaspin inhibited the accumulation of 4-HNE adducts, an indicator of ROS generation in mesenteric arterial wall of SHR (Fig.…”
Section: Discussionmentioning
confidence: 99%